Effects of Branched-Chain Amino Acids on Parameters Evaluating Sarcopenia in Liver Cirrhosis: Systematic Review and Meta-Analysis - Ismaiel, Abdulrahman; Bucsa, Camelia; Farcas, Andreea; Leucuta, Daniel-Corneliu; Popa, Stefan-Lucian; Dumitrascu, Dan L. (Frontiers in Nutrition, 2022)
Introduction: Sarcopenia is a major element of malnutrition in liver cirrhosis (LC) and is present in 30-70% of this population, being associated with a poor overall prognosis due to related complications such as hepatic encephalopathy, ascites, and portal hypertension. This systematic review and meta-analysis aimed to evaluate the effects of branched-chain amino acids (BCAA) supplementation on several anthropometric parameters used to assess sarcopenia in LC. Materials and Methods: A comprehensive systematic electronic search was performed in PubMed, EMBASE, Scopus, Cochrane Library, and ClinicalTrials.gov databases using predefined keywords. We included full articles that satisfied the inclusion and exclusion criteria. Quality assessment of included studies was conducted using Cochrane Collaboration's tool and NHLBI quality assessment tools for interventional and observational studies, respectively. The principal summary outcome was the mean difference (MD) in the evaluated anthropometric parameters. We performed a pre- and post-intervention analysis and comparison between two intervention groups (BCAA vs. controls) of the evaluated parameters when applicable. Results: A total of 12 studies involving 1225 subjects were included in our qualitative synthesis and five in our quantitative synthesis. At baseline vs. post-intervention assessment, subjects receiving BCAA supplementation were found to have a significant improvement in skeletal muscle index (SMI) (-0.347 [95% CI -0.628 – -0.067; p-value 0.015]) and mid-arm muscle circumference (MAMC) (-1.273 [95% CI -2.251 – -0.294; p-value 0.011]). However, no improvements were reported in handgrip (-0.616 [95% CI -2.818 – 1.586; p-value 0.584]) and triceps cutaneous fat (1.10 [95% CI -0.814 – 3.014; p-value 0.263]). Conclusion: Following BCAA supplementation, several anthropometric parameters used to evaluate sarcopenia in LC patients were found to be improved, including SMI and MAMC. Nevertheless, no improvements were seen in handgrip and triceps cutaneous fat. Results should be interpreted with caution due to the limited methodological quality of the included studies.